1991
DOI: 10.1136/bjsm.25.3.151
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in high-skilled and low-skilled soccer: a prospective study.

Abstract: Fifty-five male soccer players organized in three teams, one high and two lower ranking, were followed prospectively during 1 year to register the rate, type and severity of injuries in highly skilled and low-skilled players.The injury rate of the low-skilled players was significantly higher than that of the better players. The reason for this is that low-skilled players play in more competitions and this is where injuries tend to occur. When we stratified on game/practice, the low-skilled players' excess risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 10 publications
8
75
1
3
Order By: Relevance
“…These results are in line with other reports (20,4,14,19,18,22,23), in which most of the injuries occurred in the lower extremities. Inklaar (11), also concluded from his review of the literature that 61% to 90% of all injuries occurred in lower extremities.…”
Section: Discussionsupporting
confidence: 83%
“…These results are in line with other reports (20,4,14,19,18,22,23), in which most of the injuries occurred in the lower extremities. Inklaar (11), also concluded from his review of the literature that 61% to 90% of all injuries occurred in lower extremities.…”
Section: Discussionsupporting
confidence: 83%
“…Previous investigations have reported ankle injuries to be the most common injury in football (Ekstrand, 1982;Nielsen & Yde, 1989;Poulsen et al, 1991). We found that the thigh was the most common injury location, in accordance with the results from studies on English professionals (Hawkins & Fuller, 1999;Hawkins et al, 2001).…”
Section: Type and Location Of Injuriessupporting
confidence: 90%
“…Previous studies from Sweden and Denmark have reported similarly high proportions, 31-37%, of overuse injuries Nielsen & Yde, 1989;Engström et al, 1990;Poulsen et al, 1991), possibly reflecting the sometimes poor environmental and surface conditions in northern Europe.…”
Section: Type and Location Of Injuriesmentioning
confidence: 79%
See 1 more Smart Citation
“…Estos resultados corroboran lo dicho en otros estudios 12,13 donde la frecuencia de lesión disminuye de forma progresiva a lo largo de la temporada y donde el número de lesiones aumenta conforme aumenta la carga, principalmente en las primeras semanas de entrenamiento cuando el deportista todavía no se ha adaptado a los entrenamientos En la TA existe un repunte en el mes de abril al volver a aumentar el volumen con el objetivo de preparar la fase de play-off. Como ocurre en otros estudios 15 que no encontraron tendencia clara al obtener dos picos de mayor frecuencia en los meses de marzo y mayo, debido a la necesidad de alcanzar los objetivos de la temporada, lo que genera en los jugadores un mayor stress y fatiga a todos los niveles, lo que muchos autores señalan como factor de riesgo extrínseco importante a tener en cuenta 16,18,19,[35][36][37][38] . A niveles más altos de ansiedad se incrementa el riesgo de lesionarse 39 .…”
Section: Volumen De Ambas Temporadas (E/h)unclassified